DUKUNGAN SOSIAL ORANG TUA DAN KECERDASAN EMOSI TERHADAP RESILIENSI AKADEMIK PADA SISWA SMA YANG MELAKSANAKAN PEMBELAJARAN DARING - Auliya, Farhan; Ekasari, Agustina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
This study aims to determine the relationship between parental social support and emotional intelligence on academic resilience in students of SMAN 2 Cikarang Utara during online learning. This study uses quantitative methods with research design using correlation and influence research. The subjects in this study were students in grades 10, 11, and 12 of SMAN 2 Cikarang Utara with a total of 138 students. This study uses a parental social support scale with a reliability value of 0.926 Alpha Chronbach, an emotional intelligence scale with a Chronbach Alpha reliability value of 0.926 and an academic resilience scale with a Chronbach Alpha value of 0.808. The data analysis technique used rank-spearman correlation and multiple linear regression test. This study found that there is a relationship between parental social support and academic resilience and there is a relationship between emotional intelligence and academic resilience. Based on the results of multiple linear regression tests, the variables of parental social support and emotional intelligence have an effect of 57%. Students who have parental social support and high emotional intelligence have higher academic resilience than students whose parents' social support and emotional intelligence are low.